2019
DOI: 10.1002/adfm.201906311
|View full text |Cite
|
Sign up to set email alerts
|

A Visible‐ and NIR‐Light Responsive Photothermal Therapy Agent by Chirality‐Dependent MoO3−x Nanoparticles

Abstract: Chirality‐based semiconducting nanocrystals, as an emerging area, are envisioned to have great potential in chiral sensing, biomedicine, and chiroptical devices. Herein, chiral substoichiometric molybdenum oxide (l/d‐Cys‐MoO3−x) nanoparticles are synthesized via step‐by‐step reduction treatment with chiral cysteine molecules. The obtained nanoparticles are used as visible‐ and near‐infrared‐light dual responsive photothermal therapy agent for tumor cell ablation. Notably, the chiral nanoparticles show chiral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…[38,39] Thus, the MoO 3-x nanomaterials were applied in photothermal removal of cancer. [40][41][42] The convenient way to obtain MoO 3-x nanomaterials is to separate from bulk oxide [17] MoO 3 powders with an exfoliation process, which is time consuming and low yield. Generally, the extraction of MoO 3-x nanoparticles can be classified as two categories: hydrothermal and chemical exfoliation.…”
Section: Introdutionmentioning
confidence: 99%
“…[38,39] Thus, the MoO 3-x nanomaterials were applied in photothermal removal of cancer. [40][41][42] The convenient way to obtain MoO 3-x nanomaterials is to separate from bulk oxide [17] MoO 3 powders with an exfoliation process, which is time consuming and low yield. Generally, the extraction of MoO 3-x nanoparticles can be classified as two categories: hydrothermal and chemical exfoliation.…”
Section: Introdutionmentioning
confidence: 99%
“…As reported previously, the phase structure and valence state of molybdenum oxides were considered as two main factors that affect their photothermal properties [46,47]. In the present work, to understand the mechanism of enhanced photothermal effects, the effects of Mo resource dosage and reduction temperature on the photothermal properties of MoO 3−x @PPSNs were explored.…”
Section: Photothermal Properties Measurementmentioning
confidence: 79%
“…In addition, Kotov “and co‐workers [ 45 ] as mentioned in Figure 3B exhibited that nonstoichiometric WO 3− x NPs are capable for peptide catalysis. 3)Chiral nanophotonics: Deng and co‐workers [ 59 ] have highlighted that CuO/cellulose crystal (CNC) and CuO (calcinated from CuO/CNC) nanoflowers can both serves as chiral template for generating full‐color CPL when achiral fluorescent dyes are mixed with them (Figure 4C). Besides, Kotov's recent work, [ 44 ] as shown in Figure 3A, pointed out that chiral Co 3 O 4 gels can realize optical modulation via a magnetic field leading to strong absorption variation. 4)Chirality‐based therapy: Our work on nonstoichiometric chiral MoO 3− x NPs [ 60 ] showed both visible‐ and NIR‐light selective absorption due to the chirality induction by surface chiral ligands, which enables chiral MoO 3− x NPs as dual‐mode photothermal therapy (PTT) agents for cancer treatments (Figure 4D). Similarly, Kuang's work [ 2 ] as previously discussed, showed that phenylalanine‐capped Cu x O NPs can be used to scavenge ROS in vivo, therefore rescued the memory loss of mice with Parkinson's disease. 5)Chirality‐based devices: As mentioned in Figure 2D, the layer‐by‐layer nanostructure of chiral NiMoO 4 · x H 2 O photonic crystals reported by Tang and co‐workers [ 37 ] exhibited extremely large chiroptical activity ( g max ≈ −1.6) with tunable features providing possibilities for chirality‐based multifunctional devices with favorable optical, electrical, and magnetic properties.…”
Section: Applications and Perspectivesmentioning
confidence: 93%
“…Besides, Kotov's recent work, [44] as shown in Figure 3A, pointed out that chiral Co 3 O 4 gels can realize optical modulation via a magnetic field leading to strong absorption variation. 4) Chirality-based therapy: Our work on nonstoichiometric chiral MoO 3−x NPs [60] showed both visible-and NIR-light selective absorption due to the chirality induction by surface chiral ligands, which enables chiral MoO 3−x NPs as dual-mode photothermal therapy (PTT) agents for cancer treatments ( Figure 4D). Similarly, Kuang's work [2] as previously discussed, showed that phenylalanine-capped Cu x O NPs can be Reproduced with permission.…”
Section: Applications and Perspectivesmentioning
confidence: 99%